ANALISIS INTERVAL PEMELIHARAAN KOMPONEN KRITIS UNIT FUEL CONVEYOR DENGAN PENDEKATAN RELIABILITY CENTERED MAINTENANCE (RCM) - Marimin Marimin; Nabila Fatin Zulna (Jurnal Teknologi Industri Pertanian, 2022)
The scheduling of the machine maintenance system is a system that can assist companies in preventing machine damage which results in disrupted production processes. Corrective treatment methods have not been able to guarantee a smooth production process. This research will plan preventive maintenance activities to increase the reliability of production machines using the Reliability Centered Maintenance (RCM) approach. The result shows the highest downtime was boiler station with a percentage of 22.25%. The machine that works at the boiler station which has the highest level of damage was the fuel conveyor 2 with a percentage of 35.10%. The critical components which are the root causes of the highest damage problems in the fuel conveyor 2 machine were electromotor, chain coupling, and gearbox. In the electromotor, chain coupling, and gearbox components, preventive maintenance scheduling based on the results of each simulation were when t = 158, t = 190, and t = 67, respectively. The results of critical component maintenance scheduling indicated the achievement of the reliability value from before. After doing preventive maintenance, the reliability value of each component increased by 12%, 32%, and 8%, respectively. The frequency of periodic inspection every month on electromotor, chain coupling, and gearbox components were at least 4 times, 3 times, and 10 times, respectively. Keywords: downtime, maintenance, preventive maintenance. reliability, scheduling